2010
DOI: 10.1007/s10853-009-4026-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature fabrication of macroporous scaffolds through foaming and hydration of tricalcium silicate paste and their bioactivity

Abstract: A low-temperature fabrication method for highly porous bioactive scaffolds was developed. The twostep method involved the foaming of tricalcium silicate cement paste and hydration to form calcium silicate hydrate and calcium hydroxide. Scaffolds with a combination of interconnected macro-and micro-sized pores were fabricated by making use of the decomposition of a hydrogen peroxide (H 2 O 2 ) solution that acted as a foaming agent and through the hydration of tricalcium silicate cement. It was found possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Further, after the immersion into the SBF solution, two major peaks (marked as A/O in Fig. b) could be identified as carbonated apatite and/or octacalcium phosphate (OCP) as also indexed by others . The two peaks were more dominant as the immersion time progressed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Further, after the immersion into the SBF solution, two major peaks (marked as A/O in Fig. b) could be identified as carbonated apatite and/or octacalcium phosphate (OCP) as also indexed by others . The two peaks were more dominant as the immersion time progressed.…”
Section: Resultsmentioning
confidence: 90%
“…3b) could be identified as carbonated apatite and/or octacalcium phosphate (OCP) as also indexed by others. 46,48,49 The two peaks were more dominant as the immersion time progressed. The crystallographic structure of carbonated apatite, OCP, and HAp is almost similar in terms of peak position.…”
Section: Xrd Studymentioning
confidence: 97%
“…When C 11 A 7 ⋅CaF 2 is added to an inorganic solidified foam system, Al 2 O 3 , coming from the admixture, could react with gypsum to immediately form ettringite crystals (AFt), which will adhere to the particle surface [25]. At the same time, the consumption of gypsum accelerates the rate of tricalcium silicate (C 3 S) hydration, forming a small amount of fibrous CSH filling among the cement particles [26].…”
Section: Foam Stabilizer and Settingmentioning
confidence: 99%
“…For affording a 3D scaffold with good mechanical strength, compressive, bending, and potentially improving bioactivity in vivo, a ceramic-based scaffold can provide these characteristics. Several studies have been reported to fabricate a 3D ceramic-based scaffold: free casting, sacrificial template, and direct foaming/gas foaming [4,14]. The simplest way that is commonly used is gas foaming.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffold fabrication often involves a high temperature to achieve an acceptable hardness and to make it solvent-free. Nevertheless, high-temperature heating causes decreasing bioactivity and undesirable crystallisation [14]. For those reasons, the microwave heating method appears to become an alternative option for heating.…”
Section: Introductionmentioning
confidence: 99%